All Shall be Well Explorations in Universal Salvation and Christian Theology, from Origen to Moltmann. - MacDonald, Gregory (Havertown : Lutterworth Press, 2011)
Universalism runs like a slender thread through the history of Christian theology. Over the centuries Christian universalism, in one form or another, has been reinvented time and time again. In this book an international team of scholars explore the diverse universalisms of Christian thinkers from the Origen to Moltmann. In the introduction Gregory MacDonald argues that theologies of universal salvation occupy a space between heresy and dogma. The studies in this collection aim, in the first instance, to hear, understand, and explain the eschatological claims of a range of Christians from the.
12. The Judgment of Love: The Ontological Universalism of Sergius Bulgakov (1871-1974)13. ""I Do Teach It, but I Also Do Not Teach It"": The Universalism of Karl Barth (1886-1968); 14. The Totality of Condemnation Fell on Christ: Universal Salvation in Jacques Ellul (1912-1994); 15. In the End, God . . .: The Christian Universalism of J. A. T. Robinson (1919-1983); 16. Christ's Descent into Hell: The Hopeful Universalism of Hans Urs von Balthasar (1905-1988); 17. Hell and the God of Love: Universalism in the Philosophy of John Hick (1922-)
Description based upon print version of record.
18. The Annihilation of Hell and the Perfection of Freedom: Universal Salvation in the Theology of Jürgen Moltmann (1926-)Back Cover
Keywords: Universalism -- History of doctrines; Salvation -- Christianity -- History of doctrines; Universalism -- History of doctrines; RELIGION / Christian Theology / Soteriology; Electronic books